Perundungan Siber: Pencegahan Perilaku Melalui Pengenalan Aspek Hukum - Evelyn Angelita Pinondang Manurung; Maria Osmunda Eawea Monny (Fakultas Hukum, Universitas Warmadewa, 2022)
Development of technology globally, the needs of the community, especially the younger generation, for technological devices in daily activities are important. As a result of these developments, technology has gradually changed the behavior of society and human civilization globally. The development of internet technology has also caused the world to become borderless and caused significant changes in human behavior. Cyberbullying among the young generation today is an important issue that cannot be underestimated at this time. This problem can occur in any country regardless of the level of socio-economic development of a region. Cyberbullying has a negative impact on the psychological condition of victims of bullying. This research is a literature review that discusses library materials and legal materials related to cyberbullying. This study aims to determine the legal aspects related to cyber bullying behavior so that every level of society, especially the younger generation, understands and understands legal aspects such as the impact / consequences of cyber bullying behavior. This study uses a normative juridical research method using library law sources. The fact that there are many cases of cyber bullying involving students is evidence that the public's understanding of the negative impact of cyber bullying behavior is low. Every victim of bullying also deserves a sense of security and legal protection. The existence of socialization of the legal impact of cyber bullying behavior is very necessary, none other than so that cyber bullying behavior can be prevented or minimized.